THE ROLE OF BRAND IMAGE MEDIATION ON CONSUMER INTEREST IN CHOOSING UMRAH AND HAJJ SERVICES IN THE NEW NORMAL ERA - Gampo Haryono; Albetris Albetris (Management Department, Faculty of Economics and Business, Universitas Jambi, 2023)
Lately, there has been a growing interest in undertaking sustainable global tourism destinations particularly to Saudi Arabia. The benefits can be maximized if the government is successful in attracting present pilgrims and influencing their future intentions to visit the country as tourists through service providers in Muslim countries. Therefore, the purpose of this study is to measure the interest buying of pilgrims for the holy land based on the influence of E-WOM, Price, and Brand Image through the mediation model at PT Andalas Jaya Wisata in the New Normal Era. With a purposive technique with two criteria, it is planned to distribute 99 online questionnaires and direct interviews, then analyze the data with the help of Smart PLS. the results of this study show E-WOM variable on Interest Buying variable has not an effect and Price variable on Interest Buying variable has not an effect.